The effectiveness of ornamental building materials (tiles) for retrospective thermoluminescence dosimetry - Yasmin, Sabina (Elsevier, 2022)
Like many other decorative building materials, tiles are one of the most precious ornamental ingredients for making a lucrative building image. It not only offers beauty and luxury but also added value by protecting/monitoring ionizing radiation. In this study, the utmost regular use of seven varieties of tile samples has been considered for retrospective thermoluminescence dosimetry. To observe the potentials of tiles for retrospective dosimetry, the major thermoluminescence properties (such as dose-response, energy dependence, self-sensitivity, relative sensitivity, glow curves, repeatability, fading, and also effective atomic number) has been investigated following the annealing -irradiation - readout cycles. Making an allowance for the various TL parameters, White Horse (Mirror Polish) tiles demonstrate suitability to be used as emergency TL dosimeter in 0.5-100 Gy dose array. Comparing the values of Z(eff) of these numerous tiles' samples (11.6-12.7) with TLD-200 (Z(eff) = 16.3), it is to be noted that tiles can be used as a suitable material for environmental radiation dosimetry. The thermoluminescent characteristics of tiles in the dose limit from 0.5 Gy to 100 Gy are reported here for the first time.